Pendekatan Fuzzy FMEA dalam Analisis Faktor Risiko Kecelakaan Kerja - Sukwadi, Ronald; Wenehenubun, Frederikus; Wenehenubun, Tarsina Wati (Universitas Katolik Parahyangan, 2017)
This study aims to identify and analyze the risk factors of work accidents. Failure Mode and Effect Analysis (FMEA) and Fuzzy Logic approach are applied. The information obtained from the workers is expressed using fuzzy linguistics terms, and a FMEA method is proposed to determine the risk priority of failure modes. The results indicate that injuries caused when struck by an object are the highest risk factor of work accident (FRPN = 886). Some work improvements are suggested to reduce or eliminate the work risks.Keywords: Risk factors, work accident, FMEA, FuzzyÂ